2014
DOI: 10.1103/physrevb.90.104514
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electron irradiation on resistivity and London penetration depth ofBa1xKxFe2As2

Abstract: Irradiation with 2.5 MeV electrons at doses up to 5.2 ×10 19 electrons/cm 2 was used to introduce point-like defects in single crystals of Ba1−xKxFe2As2 with x = 0.19 (Tc = 14 K), x = 0.26 (Tc = 32 K) and 0.34 (Tc = 39 K) to study the superconducting gap structure by probing the effect of non-magnetic scattering on electrical resistivity, ρ(T ), and London penetration depth, λ(T ). For all compositions, the irradiation suppressed the superconducting transition temperature, Tc and increased resistivity. The low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 57 publications
(91 reference statements)
11
36
0
Order By: Relevance
“…In the optimally doped region, x ≈ 0.35 to 0.4, two effective isotropic superconducting gap scales (roughly with a 2:1 magnitude ratio) were identified in many experiments, for example, thermal conductivity ( 6 ), London penetration depth ( 7 , 8 ), and angle-resolved photoemission spectroscopy (ARPES) ( 8 12 ). In the heavily overdoped region, x ≥ 0.8, a gap with line nodes was identified by thermal conductivity ( 13 15 ), London penetration depth ( 16 ), and ARPES ( 9 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the optimally doped region, x ≈ 0.35 to 0.4, two effective isotropic superconducting gap scales (roughly with a 2:1 magnitude ratio) were identified in many experiments, for example, thermal conductivity ( 6 ), London penetration depth ( 7 , 8 ), and angle-resolved photoemission spectroscopy (ARPES) ( 8 12 ). In the heavily overdoped region, x ≥ 0.8, a gap with line nodes was identified by thermal conductivity ( 13 15 ), London penetration depth ( 16 ), and ARPES ( 9 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since these initial reports, the London penetration depth has been measured systematically in a variety of families of iron-pnictides and ironchalcogenides. [21][22][23][24][25][26][27][28][29][30][31] Perhaps the most striking recent ob-servation is a disorder-induced topological change of the superconducting gap structure, as revealed from the low-T behavior of δλ L in BaFe 2 (As 1−x P x ) 2 . 32 Nonmagnetic defects were controllably introduced by electron irradiation, and it was found that the nodal state of P-doped BaFe 2 As 2 changes to a nodeless state with increasing disorder.…”
Section: 7mentioning
confidence: 99%
“…Therefore, simultaneous measurement of another disorder-sensitive parameter, for example, London penetration depth, λ(T ), can be used to impose additional constraints on the possible pairing models. Measurements of the low-temperature variation, ∆λ(T ) = λ(T ) − λ(0), can be used to study the gap anisotropy [7,8] and to distinguish between s ± and s ++ pairing [5]. The latter was successfully used to study nodal BaFe 2 (As,P) 2 [9] and SrFe 2 (As,P) 2 [7] where potential scattering lifted the nodes proving them accidental, therefore strongly supporting s ± pairing.…”
mentioning
confidence: 99%